The Use of Instagram as a Media to Teach Students' Writing Recount Text - Siti Sholikhah; Muh Syafei; Aisyah Ririn Perwikasih Utari (Prominent, 2019)
Abstract. The objective of this research is to find out whether there is a significant difference between students’ writing recount text before and after being taught by using Instagram as a media or not. In this research, the researcher used quantitative method and used quasi-experiment as the design of the research. The number of sample is 36 students from X MIPA 4 which are taken by using cluster random sampling technique. The researcher uses test as the instrument of the research. The test is in the form of writing test to know the students’ writing ability before and after being taught by using Instagram as a media. The result of the research shows that the students’ mean score have an improvement from 6.8 to 8.8 and from good categorize to excellent categorize. And the standard deviation from the students score has decreased from 0.89 to 0.83 which means that the students’ post-test score is well distributed than the pre-test score. The calculation of t-test shows that the Ho is rejected and Ha is accepted. It is because the to (t obtain) falls in the critical region and to (t obtain) is more than tt (t critical). The to (t obtain) is 5.3 while the tt (t critical) is 2.042. In conclusion, there is a significant difference between students’ writing recount text before and after being taught by using Instagram as a media.  Key Words: Instagram, Media, Recount Text, English Writing